Reduced graphene oxide/metallic MoSe2: Cu nanosheet nanostructures grown by a chemical process for highly efficient water splitting. (March 2019) - He, H.-Y.; He, Z.; Shen, Q.
Graphical abstract: Highlights: RGO/1T-MoSe2 : Cu nanosheet nanostructures were synthesized by chemical process. RGO incorporation introduces interface effect and decreased the average particle size. Cu doping decreased average particle size and increased electrical conductivity. Cu doping and RGO incorporation enhanced the hydrogen evolution catalytic properties. Abstract: The transition metal dichalcogenides with metallic 1T structure are attracting contemporary attention for applications in high-performance devices because of their peculiar optical and electrical properties. To date, one-step synthesis of 1T-MoSe2 is a challenge. This work presents a facile one-step synthesis of reduced graphene oxide/1T MoSe2 : Cu nanosheets. The experiment results indicated that the MoSe2 prepared by simple chemical solution reaction possessed 1T structures. The reduced graphene oxide (RGO) incorporation and Cu doping did not obviously affect the phase structure but decreased the average particle size. The 1T structure, together with the Cu doping and interface effect between the MoSe2 and RGO, remarkably enhanced the conduction and photoconduction of the nanostructures. Thus, Cu doping and RGO incorporation also enhanced the hydrogen evolution catalytic activity and stability, making the RGO/MoS2 : Cu nanosheet a most active and stable catalyst for hydrogen evolution.